Pengaruh Experiential Marketing dan Price Bundling terhadap Consumer Purchase Interest - Salma Athifah Azhar; R. Oktini, Dede; Malik Akbar Rohandi, Mochamad (Bandung Conference Series: Business and Management, 2024)
Abstract. Intense competition in the muslim fashion industry drives companies to compete for market share. To attract attention and meet market demand, companies need to develop marketing strategies that align with consumer desires and needs. This study examines the impact of experiential marketing and price bundling on consumer purchase interest at Shopee Orianara Official Shop. The research employs descriptive and verificative analysis with a quantitative approach, utilizing multiple linear regression and hypothesis testing. The sampling technique used is purposive sampling with 110 respondents, and data is collected through questionnaires. The results indicate that both experiential marketing and price bundling have a positive and significant effect on consumer purchase interest. Simultaneously, experiential marketing and price bundling have a positive and significant effect on consumer purchase interest. Abstrak. Persaingan ketat dalam industri fashion muslim membuat perusahaan berlomba-lomba merebut pasar. Untuk menarik perhatian dan memenuhi permintaan pasar, perusahaan perlu mengembangkan strategi pemasaran yang sesuai dengan keinginan dan kebutuhan konsumen. Penelitian ini mengkaji pengaruh experiential marketing dan price bundling terhadap consumer purchase interest di Shopee Orianara Official Shop. Metode yang digunakan adalah analisis deskriptif dan verifikatif dengan pendekatan kuantitatif melalui analisis regresi linear berganda dan uji hipotesis. Teknik sampling menggunakan purposive sampling dengan 110 responden. Pengumpulan data melalui kuesioner. Hasil penelitian menunjukkan bahwa experiential marketing dan price bundling masing-masing berpengaruh positif dan signifikan terhadap consumer purchase interest. Secara simultan, experiental marketing dan price bundling berpengaruh positif dan signifikan terhadap consumer purchase interest.